The data revolution : big data, open data, data infrastructures and their consequences - Kitchin, Rob, (SAGE, 2014)
A seminal text, written by one of the world's leading experts in the field. In contrast to the hype and hubris of much media and business coverage, it provides a synoptic and truly critical analysis of 'big data', 'open data' and the emerging data landscape.